A glossary of terms for navigating the field of social network analysis. Issue 12 (16th November 2004) - Hawe, Penelope; Webster, Cynthia; Shiell, Alan
Abstract : Social network analysis is the study of social structure. This glossary introduces basic concepts in social network analysis. It is designed to help researchers to be more discriminating in their thinking and choice of methods.